The Influence of Brand Image and Hedonic Lifestyle on iPhone Purchase Decisions Among Generation Z Women in Cirebon City - Sasikirana, Diva; Masruroh, Sri; Hernidatiantin, Lis Tatin (Indonesian Journal of Advanced Research, 2025)
The research conducted aims to analyze the influence of brand image and hedonistic lifestyle on the decision to buy an iPhone among Generation Z women in Cirebon City. Generation Z, known as the digital generation, shows a high interest in technology products, especially smartphones. Quantitative research methods and survey approaches are utilized, and data is obtained by distributing questionnaires to respondents. The results of the analysis obtained state that Brand image has a positive and significant influence on the decision to buy an iPhone, with a t-value of 1.714 and a significance of 0.000. Hedonic lifestyle also contributes positively, with a t-value of 4.015 and a significance of 0.000. The F test states that simultaneously, both variables have a significant influence on the decision to buy. The findings obtained provide useful knowledge to marketers in planning more effective marketing strategies to attract consumers in this segment.